2021
DOI: 10.26811/peuradeun.v9i2.518
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Victimization Among Junior High School Students in Aceh, Indonesia: Prevalence and its Differences in Gender, Grade, and Friendship Quality

Abstract: This study aimed to describe the prevalence of bullying victimization and its differences in gender, grade level, and friendship quality among junior high school students in Aceh, Indonesia. The study also investigated the moderation effect of gender on the association between friendship quality and bullying victimization. A total of 360 students from four schools in Banda Aceh was selected using Cluster and Disproportionate Stratified random sampling. The Revised Olweus Victim Questionnaire and Friendship Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Multiple studies from many countries have reported different prevalence rates of bullying victimization among adolescents aged 12–18 years: less than 10% in Asian countries (Hongkong, Taiwan, and Macao) [ 8 ], 17.9% in Pakistan [ 9 ], around 20% in the United States [ 10 ], more than 40% in African countries (Malawi and Ghana) [ 11 , 12 ], 40.6% in Philippines [ 13 ], 46.9% in Indonesia [ 14 ], and 47% in New Zealand [ 15 ]. The UNESCO report (2019) estimated that 32% of children and adolescents are experiencing bullying victimization in some form worldwide [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies from many countries have reported different prevalence rates of bullying victimization among adolescents aged 12–18 years: less than 10% in Asian countries (Hongkong, Taiwan, and Macao) [ 8 ], 17.9% in Pakistan [ 9 ], around 20% in the United States [ 10 ], more than 40% in African countries (Malawi and Ghana) [ 11 , 12 ], 40.6% in Philippines [ 13 ], 46.9% in Indonesia [ 14 ], and 47% in New Zealand [ 15 ]. The UNESCO report (2019) estimated that 32% of children and adolescents are experiencing bullying victimization in some form worldwide [ 16 ].…”
Section: Introductionmentioning
confidence: 99%